Efeitos da exposição à lambda-cialotrina no teleósteo Brycon amazonicus: metabolismo antioxidante, parâmetros histológicos e hematológicos - Venturini, Francine Perri (Universidade Federal de São Carlos, 2014)
Currently, in Brazil, there has been noticed increases of agrochemicals use, in spite the trend of using less toxic products. Pyrethroids appear as the option due to low toxicity displayed to birds and mammals, and the low bioaccumulation along the trophic chain. The pyrethroid insecticide λ-cyhalothrin (LCH) is used against a variety of arthropods. These chemicals can reach aquatic environments either by direct application in fish farms to kill parasites or by runoff after agricultural and domestic use, then affecting non-target organisms. We dealt with evaluation of antioxidant responses of matrinxã, Brycon amazonicus, exposed to LCH (TrincaCaps® DVA) and its recovery, since this is a freshwater fish relevantly farmed in Brazil. Twelve fish (n=12) were exposed to 0.65 μgL-1 (10% of the LC50;96h) for 96 hours and allowed to recover in a xenobiotic free water for 7 days. Hematological, osmoregulatory, antioxidant, neurotoxic, histologic and genotoxic effects were evaluated after sub-lethal exposure and recovery. LCH was extremely toxic to B. amazonicus since the LC50;96h was below 0.1 mgL-1. After the exposure span, fish exhibited impairment of respiratory functions and hypovolemia; the hematological parameters were not completely reestablished, despite a tendency to recover. The osmotic balance was affected after exposure, and it was not completely restored after recovery. The activity of brain acetylcholinesterase did not depict any change after both evaluation periods. Antioxidant defenses were activated in liver, kidney and gills, but this fact was not enough to prevent lipid peroxidation. After recovery, some defenses remained activated; nevertheless no lipid peroxidation was observed in any tissue. Histological parameters indicated liver and kidney injury, but no one was observed in gills. The kidney morphology was severely affected, but was reestablished after recovery; an opposite response was observed in liver. Micronuclei and nuclear alterations in erythrocytes were not observed after either exposure or recovery. We call attention to the hepatotoxic and nephrotoxic potential of LCH in B. amazonicus, emphasizing the importance of substantial studies to ground its use regulations in agriculture and aquaculture activities, since the set of injuries observed poses risk to this fish species.
Keywords: Bioquímica; Estresse oxidativo; Marcadores biológicos; Inseticida piretróide; Fauna neotropical; Biochemistry; Oxidative stress; Pyrethroid insecticide; Neotropical fish; CIENCIAS BIOLOGICAS::GENETICA